Issue Information. Issue 9 (September 2016) - Unknown
Abstract : COVER PHOTOGRAPH : Mirrored images of mt‐mmpB expression in dorsoventral muscle cells that are in close proximity to neoblasts. From A muscle‐derived matrix metalloproteinase regulates stem cell proliferation in planarians ; Caitlin B. Dingwall and Ryan S. King; Developmental Dynamics 245:963–970. Read the full article at DOI:10.1002/dvdy.24428